Exploring the Students’ Voices on the Use of Wordshake and Shusi Spell Games to Teach English Vocabulary - Aniuranti, Asfi; Hidayah, Arini (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The vocabulary teaching process has been discussed widely, and the studies that are concerned with the strategies for teaching English vocabulary were explored by many researchers. However, research about students’ voices is commonly neglected. This descriptive quantitative research aims to fill this gap by investigating students' perceptions of Wordshake and Shusi Spell games as tools for teaching English vocabulary. The two games were employed in Lexical Studies 1 class for seven meetings as ice-breaking activities. Then, the students (16 students) had to complete a closed questionnaire. The data were examined by finding out the percentage of every item in the questionnaire. The results showed two significant findings. Firstly, the students agreed that the games affected them positively. Secondly, the games influenced the teaching and learning process positively. In short, Wordshake and Shusi Spell got students’ positive responses.